(untitled) (Global Journal of Management and Business Research, 2018)
The article analyzes the economic and social development of the Republic of Uzbekistan. The analysis used indicators such as the increase in the share of paid services rendered to the population in the gross regional product, the growth of employment in the service sector. The main factors influencing the efficiency of the service sector are identified.